2018
DOI: 10.1186/s13007-018-0352-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral imaging: a novel approach for plant root phenotyping

Abstract: BackgroundRoot phenotyping aims to characterize root system architecture because of its functional role in resource acquisition. RGB imaging and analysis procedures measure root system traits via colour contrasts between roots and growth media or artificial backgrounds. In the case of plants grown in soil-filled rhizoboxes, where the colour contrast can be poor, it is hypothesized that root imaging based on spectral signatures improves segmentation and provides additional knowledge on physico-chemical root pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 80 publications
1
37
0
Order By: Relevance
“…The results indicated that the correlation between the hyperspectral data of corn and the whole seedling length is small, so it is difficult to accurately predict the whole seedling length through hyperspectral images. The correlation between hyperspectral characteristics and different germination characteristics (seedling root length, seedling length,) was different, which was consistent with the results in [ 44 ]. The strong correlation between the seed and the root length after germination was also verified by the experiment in [ 45 ].…”
Section: Resultssupporting
confidence: 90%
“…The results indicated that the correlation between the hyperspectral data of corn and the whole seedling length is small, so it is difficult to accurately predict the whole seedling length through hyperspectral images. The correlation between hyperspectral characteristics and different germination characteristics (seedling root length, seedling length,) was different, which was consistent with the results in [ 44 ]. The strong correlation between the seed and the root length after germination was also verified by the experiment in [ 45 ].…”
Section: Resultssupporting
confidence: 90%
“…HSI acquires more comprehensive information about samples. Hyperspectral imaging is widely studied in the fields of agriculture [12,13], food [14], medical [15], and pharmaceutical [16], to name a few. Moreover, hyperspectral imaging is also studied in the tea industry for tea quality inspection [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The throughput was 60 rhizotrons per hour out of a total capacity of 72 rhizotrons (Nagel et al, 2012). Moreover, additional sensors (i.e., hyperspectral) were integrated into this phenotyping system with the potential to dynamically reflect root chemical components, such as root water content and lignin change (Bodner et al, 2018). X-ray CT, a 3D structural imaging application, can be used to visualize the inner 3D volume according to the differences in the X-ray attenuation of different materials, such as roots and soil.…”
Section: Going Underground: An Added Challenge In Plant Phenotypingmentioning
confidence: 99%